Social Responsibility Messages and Worker Wage Requirements: Field Experimental Evidence from Online Labor Marketplaces - Burbano, Vanessa C. (Organization Science, 2016)
This paper examines the effects of employer social responsibility on the wages workers demand through randomized field experiments in two online labor marketplaces. Workers were recruited for short-term jobs and I manipulated whether or not they received information about the employer’s social responsibility. I then observed the payment workers were willing to accept for the job. In the first experiment, information about the employer’s social responsibility marginally reduced prospective workers’ wage requirements on average and had a significant effect on the highest performers, who were willing to give up the wage differential they would otherwise demand. In the second, prospective workers submitted 44% lower wage bids for the same job after learning about the employer’s social responsibility. This paper provides causal empirical evidence of a revealed preference for social responsibility in the workplace, and of a greater preference among the highest performers. More broadly, it provides evidence that workers value purpose and meaningfulness at work, and it demonstrates that workers are willing to give up pecuniary benefits for nonpecuniary benefits. It furthermore highlights heterogeneity in worker preferences for nonpecuniary benefits by worker performance type.